Normalizing failure: when things go wrong in participatory marine social science fieldwork. (19th September 2022) - Cvitanovic, C; van Putten, E I; Tuohy, P; Annand-Jones, R
Abstract: Failure is a normal and critical part of the scientific process; however, the admittance of failure remains largely stigmatized within the sciences. In this paper, we argue that sharing stories of failure should be normalized, not only for the advancement of knowledge and improvement of research outcomes, but also for the health and well-being of the scientific community. We feel that this is particularly important for early career researchers, as it will help to set more realistic expectations of a career in science and to help reframe failure as a positive force for good. To do so, we draw upon our recent experiences of failure in participatory marine social science fieldwork. We share our personal perspectives of, among other things, how we felt when confronted with failure in the field, and more importantly, the strategies we used to confront, deal with, and overcome those failures. By doing so, we generate a list of practical steps and considerations that marine social science researchers can follow to help them navigate their own failures in the field, should they occur.